1979
DOI: 10.3758/bf03209651
|View full text |Cite
|
Sign up to set email alerts
|

Generalization of the CS- preexposure effect transfers to taste- aversion learning

Abstract: Rats repeatedly exposed to a maple, vanilla, banana, or water solution were subsequently poisoned with lithium chloride after drinking the maple solution. Subjects preexposed to water showed the strongest aversions to maple, followed, in descending order, by rats preexposed to banana, vanilla, and maple. These results suggest that the effects of prepoisoning experience with a novel flavor generalized to the maple CS and interfered with the development of the maple aversion. The technique reported here is poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The apparent differences between the tastes involved tend to support these investigators in their contention that they were observing the consequence of prior exposure to novel tastes per se rather than stimulus generalization; however, the broad generalization across tastes recently observed by Dawley (1979) indicates that stimulus generalization may have influenced some of these studies. Braveman and Jarvis (1978) and Austin (Note I), using single-bottle tests, found that prior exposures to novel substances reduced neophobia in adult animals.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…The apparent differences between the tastes involved tend to support these investigators in their contention that they were observing the consequence of prior exposure to novel tastes per se rather than stimulus generalization; however, the broad generalization across tastes recently observed by Dawley (1979) indicates that stimulus generalization may have influenced some of these studies. Braveman and Jarvis (1978) and Austin (Note I), using single-bottle tests, found that prior exposures to novel substances reduced neophobia in adult animals.…”
mentioning
confidence: 59%
“…Previous research on these issues appears, in the light of Dawley's (1979) data, to have possibly been affected by stimulus generalization between flavors. Braveman and Jarvis (1978) made the best effort to date to examine the influence of stimulus generalization in this paradigm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that prior experience with a flavor different from the CS can similarly attenuate a conditioned aversion (Dawley, 1979;Kraemer & Roberts , 1984). The conventional interpretation of the preexposure effect has been that a prior flavor experience in some way disrupts the acquisition of a CS aversion, and a variety of mechanisms have been offered to account for this putative disruption (Best & Barker, 1977;Best & Gemberling, 1977;Kalat & Rozin, 1973).…”
mentioning
confidence: 99%
“…Nonreinforced preexposure to a CS, or to a stimulus similar to the CS, decreases the subsequent strength of conditioned responding expressed to the CS (Dawley, 1979;Lubow, 1973;Mackintosh, 1983). This wellestablished phenomenon, termed latent inhibition (LI), has appeared across a wide range of CSs, USs, and proeedures (Albert & Ayres, 1989;Elkins, 1973;Lubow, Markman, & Allen, 1968;Lubow & Moore, 1959;Reiss & Wagner, 1972).…”
mentioning
confidence: 99%